REGULATORY READINESS OF HALAL TOURISM DESTINATIONS DEVELOPMENT IN WEST KALIMANTAN - Nurlia; Aiyub Anshori; Ita Nurcholifah (ITB AAS INDONESIA Surakarta, 2026)
This research sought to represent the various halal destinations in Sambas Regency. The tourism industry contributes to the economic development of numerous districts. It is not difficult to develop halal tourism in West Kalimantan, in general and in Sambas Regency in particular, because the Muslim population is large and the region offers a variety of natural and cultural tourist attractions. All of its strategically significant tourist locations are expected to contribute to the growth of halal tourism. As a result, the purpose of this research is to describe tourist attractions as one of the most important locations worldwide. Instead of relying on specific concepts or theories to describe halal tourism, this study employs a qualitative descriptive approach using content analysis. According to the study, West Kalimantan is one of the provinces with a diverse range of tourism destinations, including religious, cultural, maritime, and natural landmarks. Geographically, the region shares a direct border with Sarawak in East Malaysia. Sambas Regency is one of the cross-border entries that have been formally opened, along with PLBN Aruk. Unfortunately, although the majority of the population is Muslim, no standards define a clear concept of halal tourism. However, there are no Sharia-compliant travel agencies, Sharia tour guides, or Sharia tour packages available; Kal-Bar has not been listed in the central government's halal tourism destination program; and there are no halal-certified hotels.